The inflation-targeting policy of the national bank of Ukraine in the context of international experience - Сищук, Андрій Артемович; Syshchuk, Andrii A. (Державний вищий навчальний заклад "Ужгородський національний університет", 2016)
The object matter of the inflation targeting policy in the international context and the perspectives of its usage by the National bank of Ukraine to restore the growth of the Ukrainian economy are analyzed. The international experience and consequences of the inflation targeting in different countries, goals and features of a practical implementation this policy after the global financial economic crisis in 2008-2009 are shown in this article.
Політика інфляційного таргетування Національного банку України в контексті міжнародного досвіду
Keywords: anti-inflationary policy; inflation targeting; Central Bank